Protection effectiveness and sea urchin predation risk: The role of roving predators beyond the boundaries of a marine protected area in the Western Mediterranean Sea. Issue 7 (22nd April 2022) - Farina, Simone; Ceccherelli, Giulia; Piazzi, Luigi; Grech, Daniele; Panzalis, Pieraugusto; Navone, Augusto Giuseppe; Guala, Ivan
Abstract: Effective marine protected areas (MPAs) increase top predator density. Accordingly, a large abundance of predatory fish potentially increases predation risk for sea urchins inside an MPA. Intensity of predation was investigated for the sea urchin Paracentrotus lividus at a Mediterranean MPA. Predation rates were estimated for three levels of protection (full, partial, and absent) and two habitats (rocky reefs and Posidonia oceanica meadows). The natural density of sea urchins was correlated with predator biomass (fish sparids Diplodus spp. and Sparus aurata and the gastropod Hexaplex trunculus ), and predation risk was evaluated through a tethering experiment. Significantly higher fish predation was found on the rocky reefs of the fully and non‐protected areas than in the partially protected area. These findings are consistent with the sparid biomass estimated in the fully and partially protected areas. However, a discrepancy between high predation risk and low sparid biomass was detected outside of the MPA's northern boundary, where marine farms (fish and mussels) are present. Benthic predator biomass also increased significantly across the northern boundary, but its predation activity was negligible. The low predatory fish biomass and low sea urchin density suggest a top‐down control by roving predatory fish on the rocky reefs of the non‐protected area, in proximity to the fish farms. Similarly, a significant gradient of benthic predator biomass and low sea urchin density suggest potential predation interactions inside the P. oceanica meadows across the northern MPA boundary near the mussel farms. This study highlights deviations from the expected trophic interactions outside the MPA that could be caused by aquaculture activities. Our understanding of the potential synergies between the MPAs and the nearby human activities needs to be broadened to improve the effectiveness of both ecosystem conservation and resource management.